(untitled) (Bangladesh Critical Care Journal, 2025)
Introduction: Laparoscopic ventral hernia repair (LVHR) was first described in 1992 by Karl Leblanc and has increasingly gained popularity in this current era of minimal access surgery. Compared to the open technique, laparoscopic repair has low rates of complications and recurrence, greater patient acceptance, and shorter hospital stay. Objective: This study aimed to assess the efficacy of the Laparoscopic intra-peritoneal onlay mesh with defect closure (IPOM PLUS) technique by using optimized composite mesh in ventral hernia repair. Methods: This is an observational study, carried out on 45 patients who underwent Laparoscopic ventral hernia repair by IPOM Plus technique between January 2023 to December 2023 at BIRDEM General Hospital, Dhaka. Patient demographics, perioperative data, and postoperative outcomes were recorded and analyzed. Patients who had ventral hernia with a defect size> 2 cm but < 8 cm were included in this study. Intracorporeal suture closure of all ventral hernias with defect size >2 cm was done using PBT non absorbable wound closure device (V-Loc). Optimized composite mesh (ParietexTM) with pre-placed sutures in four sites were used as prosthesis and fixed with non-absorbable tacking device. Follow up period was one year. Results: A total of 45 patients underwent Laparoscopic IPOM Plus repair of ventral hernias. The mean operative time was 90 minutes, and the mean hospital stay was 3.5 days. Intraoperative and postoperative complications were negligible. No bulging of mesh, intestinal obstruction, mesh infection and recurrence observed in one year follow up time. Complications were minimal: seroma (2.2%), port site infection (4.4%). Conclusions: The LIPOM Plus technique for ventral hernia repair demonstrated low complication and recurrence rate, high patient satisfaction, and a favorable recovery profile. These findings support LIPOM Plus as a viable and effective approach for ventral hernia management, warranting further investigation in diverse settings. Bangladesh Crit Care J September 2025; 13 (2): 104-109